2019
DOI: 10.7575/aiac.alls.v.10n.4p.14
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Turkish Language and Turkish Language and Literature Teacher Candidates’ Critical Reading Self-efficacy (The Case of Mehmet Akif Ersoy University)

Abstract: The basic purpose of native language teaching is ensuring that students develop their skills in four basic language skills at an adequate level. For this purpose, Turkish Language and Turkish language and literature teachers who work in different teaching levels, especially classroom teachers, have important duties. Reading, which is among basic language skills, is a comprehension ability for individuals to reach new information and improve themselves. The thing that is important in reading is combining new in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Most of the teachers and students explained effective learning with the elements of constructivist and cognitive theories since they believe in the effect of active participation, reading habit, self-discovery and curiosity (Altun & Çolak, 2011, Schunk, 2012Woolfolk, 2016). As it was mentioned in the introduction of the study, Turkish Language and Literature is the key course to let the students gain reading habit (Aytaç & Kaygısız, 2019;Bağcı, 2019); and the teachers and students who par-ticipated in this study also mentioned that strongly. Another stress that teachers made was on students' differences.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 64%
See 1 more Smart Citation
“…Most of the teachers and students explained effective learning with the elements of constructivist and cognitive theories since they believe in the effect of active participation, reading habit, self-discovery and curiosity (Altun & Çolak, 2011, Schunk, 2012Woolfolk, 2016). As it was mentioned in the introduction of the study, Turkish Language and Literature is the key course to let the students gain reading habit (Aytaç & Kaygısız, 2019;Bağcı, 2019); and the teachers and students who par-ticipated in this study also mentioned that strongly. Another stress that teachers made was on students' differences.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 64%
“…Teachers believe that, instead of a mechanic and chronological way of presenting the course, it should be enriched by discussions, interpretations and creative thinking activities (Göçer, 2016). Also, studies suggest that to raise students' reading habits, which has a great role in improving metacognitive skills, the key course is Turkish Language and Literature course (Aytaç & Kaygısız, 2019;Bağcı, 2019). According to OECD data (2018), the reading performance of Turkish students is not among the top countries, on the contrary, it is in one of the lowest rate countries.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…Similarly, Can and Bicer (2021) revealed that reading habit is an important predictor of critical reading skills. Similarly, in his study, Bagci (2019) determined that reading habits positively affect critical reading self-efficacy perceptions. Kosem (2019) also determined that there is a significant relationship between preservice teachers' reading attitude and critical reading self-efficacy perception levels.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, Yildiz et al (2013) adapted the Adult Reading Motivation Inventory into Turkish; Kurnaz (2019) also developed the Reading Intrinsic Motivation Scale. There are studies examining preservice teachers' critical reading perceptions and levels (Aybek & Aslan, 2015;Bagci, 2019;Cam Aktas, 2016;Kaplan, 2021;Karasakaloglu et al, 2012b;Maltepe, 2016;Ulu et al, 2017); reading motivation (Baba Basara Baydilek et al, 2018;Gecgel et al, 2020;Savaskan & Ozdemir, 2017;Soyucok & Balantekin, 2021), and metacognitive reading strategies (Babacan, 2012;Demir, 2022;Emre, 2019;Kana, 2015;Ozdemir, 2018;Ozden, 2018;Uyar et al, 2012). However, no study was found in which all three variables were used together.…”
Section: Significance and Purpose Of The Studymentioning
confidence: 99%
“…High level of self-efficacy is revealed to contribute to learners' growth in reading (Capara et al, 2008). Several studies have reported the higher self-efficacy beliefs, the better results in developing reading comprehension (Bağcı, 2019;Barkley, 2006;Cho et al, 2015;Forzani et al, 2021;Hedges & Gable, 2016;McLean & Poulshock, 2018;Peura et al, 2019;Ronimus et al, 2020;Soland & Sandilos, 2020;Tremblay & Gardner, 1995;Unrau et al, 2018). Basically, attitudes towards reading could influence reading self-efficacy of an individual; for instance, individuals who enjoy reading are shown to have higher levels of reading self-efficacy in comparison to the ones not enjoying reading (Burrows, 2012;Carroll & Fox, 2017).…”
Section: Introductionmentioning
confidence: 99%